COMPARATIVE EFFICACY OF FUNGICIDES, SELECTED BOTANICALS AND TRICHODERMA VIRIDE AGAINST EARLY BLIGHT (ALTERNARIA BRASSICICOLA) OF MUSTARD (BRASSICA JUNCEA L.) - PRABHAT PAL SINGH,; SOBITA SIMON,; MALTI DEVI PATEL, (The Bioscan, 2015)
A field experiment was conducted at the research field of the Department of Plant Pathology, SHIATS, Allahabad, (UP) during the rabi season of 2013-14 by seed treatment and foliar sprays of fungicides, plant extracts and bioagent. the crop was grown by adopted good agronomic practices and data was recorded as per cent disease severity on leaves at 60, 75 and 90 days after sowing, and pods at 75, 90 and 105 days after sowing. Results revealed that the foliar spray of mancozeb @ 2.5 g/L significantly reduced the Alternaria blight and increased yield (14.17 q/ha), highest benefit cost ratio (1:2.98 %) followed by Trichoderma viride (seed tretment @10 g/kg and foliar spray @ 10 g/L), Bavistin 50 WP (seed treatment @ 2 g/kg and foliar spray @ 2g/L), Propicanazole (seed treatment @ 1 % and foliar spray @ 1 %), Iprodine + carbendazim ( Foliar spray @ 2% ), Allium sativam (foliar spray @ 1% w/v) and Azadirachta indica (foliar spray @ 1% w/v).